The beetroot (Beta vulgaris L. ) juice on the handling of anemia in third-trimester pregnant women - Irwana Wahab; Dewi Setiyawati; Siti Hadijah (Jurnal Kesehatan Ibu dan Anak, 2022)
Anemia in pregnancy can be detrimental to the health of the mother and child. Handling anemia can be done non-pharmacologically by giving beetroot which is one of the benefits of anti-anemia. Beetroot is a vegetable that is safe for pregnant women. The purpose of this study was to analyze the effect of giving beetroot juice on the incidence of anemia in third-trimester pregnant women in the working area of Syamtalira Bayu Public Health Center. This study used a quasi-experimental research design with a pre and post-test group design approach. This research was carried out in the working area of the Syamtalira Bayu Public Health Center from July to September 2021. The sample consisted of 10 people. A dependent t-test was utilized for bivariate analysis. The results showed that the p-value was 0.000, which means that there is an effect of giving beetroot juice to decrease cases of anemia in third-trimester pregnant women. Anemia in third-trimester pregnant women is affected by giving beetroot juice for 7 days at the same time as consuming Fe tablets. Pregnant women must maintain their health so that the fetus in their womb can grow and develop with quality.